A high-strength semi-solid die-casting aluminum alloy and preparation method thereof
By using boron-doped graphene loaded with cerium oxide for high-temperature stirring and vibration treatment in the semi-solid processing of aluminum alloys, the problem of rough semi-solid processing technology of existing aluminum alloys is solved, and the high strength and plasticity of aluminum alloys are achieved, meeting the needs of industrial production.
Patent Information
- Application Number
- CN202410979772.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-07-22
AI Technical Summary
The existing semi-solid processing technology of aluminum alloys is rough, which makes it difficult for the strength and plasticity of aluminum alloys to meet the needs of industrial production.
The boron-doped graphene loaded with cerium oxide was used to stir and vibrate the high-temperature molten liquid-phase aluminum alloy to prepare a semi-solid slurry with a temperature of 580-600°C, and a high-strength semi-solid die-casting aluminum alloy was obtained by die-casting, solution treatment and aging treatment.
It significantly improves the strength and plasticity of aluminum alloys, and meets the needs of high-strength, high-toughness and high-density aluminum alloy components.
Smart Images

Figure BDA0004955702270000081 
Figure BDA0004955702270000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloy processing, in particular to a high-strength semi-solid die-casting aluminum alloy and a preparation method thereof. Background Art
[0002] Semi-solid die casting refers to the process of strong stirring during the solidification of liquid metal, so that the dendrite network skeleton that is easy to form in ordinary casting is broken into a dispersed granular structure, thereby making semi-solid metal liquid, which is then die-cast into blanks or castings. Compared with ordinary casting, semi-solid die casting has a small solidification shrinkage rate, which can avoid defects such as shrinkage cavities and looseness, and produce various parts with thinner wall thickness, denser structure and higher mechanical properties.
[0003] Aluminum alloy is a metal material that is widely used in industrial production. With the development of social economy, the demand for high-strength, high-toughness, and high-density aluminum alloy parts in the fields of automobiles, electronic appliances, and high-end equipment is increasing. The semi-solid processing technology of aluminum alloys has made certain progress, but there are still certain problems. For example, the semi-solid processing technology of aluminum alloys is rough, which makes it difficult for the strength and plasticity of aluminum alloys to meet production needs. Therefore, it is necessary to modify the existing process. Summary of the invention
[0004] The object of the present invention is to provide a high-strength semi-solid die-casting aluminum alloy and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-strength semi-solid die-casting aluminum alloy and a preparation method thereof, comprising the following steps:
[0006] Step 1: heat a silicon source, a magnesium source, a copper source, an aluminum source, a titanium source, a vanadium source, and an antimony source to 700-800° C. and melt them into a liquid state to obtain a liquid aluminum alloy;
[0007] Step 2: adding boron-doped graphene loaded with cerium oxide to the liquid aluminum alloy, heating to 1200-1400° C., keeping the temperature for 200-240 minutes, and then preparing an aluminum alloy semi-solid slurry with a temperature of 580-600° C. by a stirring and vibration method;
[0008] Step 3: die-casting the semi-solid aluminum alloy slurry to obtain a semi-solid die-cast aluminum alloy;
[0009] Step 4: subjecting the semi-solid die-cast aluminum alloy to solution treatment, water quenching and aging treatment, and furnace cooling to obtain a high-strength semi-solid die-cast aluminum alloy.
[0010] Furthermore, in step 1, the contents of various elements in the liquid aluminum alloy, by weight percentage, are 6-9.5% silicon, 0.3-0.65% magnesium, 0.15-0.25% copper, 0.06-0.09% titanium, 0.1-0.18% vanadium, 0.05-0.12% antimony, 0.01-0.2% iron, and the rest are aluminum and other impurity elements.
[0011] Furthermore, in step 2, the amount of boron-doped graphene loaded with cerium oxide is 0.8-2% of the total weight of the aluminum alloy semi-solid slurry.
[0012] Furthermore, in step 2, the preparation method of boron-doped graphene loaded with cerium oxide is:
[0013] S1: After mixing and grinding graphene oxide and boric acid for 15 to 30 minutes, heating to 900 to 1000°C at a heating rate of 10 to 15°C / min in a nitrogen environment, keeping the temperature for 60 to 90 minutes, cooling naturally, washing with ethanol, and vacuum drying to obtain boron-doped graphene;
[0014] S2: Add boron-doped graphene to ethylene glycol, stir magnetically for 15 to 30 minutes, and ultrasonically disperse for 30 to 60 minutes to obtain a boron-doped graphene dispersion; add cerium nitrate solution to the boron-doped graphene dispersion, ultrasonically disperse for 5 to 10 minutes, and then place it in a drying oven for hydrothermal reaction at 130 to 150°C for 24 hours; after the reaction is completed, cool and remove the supernatant, centrifuge, wash, dry, and grind the product, and then heat it to 400 to 500°C at a heating rate of 2 to 5°C / min in an air atmosphere, and calcine it at this temperature for 3 to 4 hours to obtain boron-doped graphene loaded with cerium oxide.
[0015] Furthermore, in S1, graphene oxide and boric acid are mixed and ground in a mass ratio of (2 to 2.2):1.
[0016] Furthermore, in S2, the concentration of the boron-doped graphene dispersion is 1-2 mg / mL; and the concentration of the cerium nitrate solution is 10-20 g / mL.
[0017] Furthermore, in step 2, the contents of the components in the boron-doped graphene loaded with cerium oxide are, by weight percentage, 25-45% cerium oxide and 55-75% boron-doped graphene.
[0018] Furthermore, in step 3, the die-casting temperature is 300-350° C., the injection speed is 1.5-2.5 m / s, the injection pressure ratio is 30-50 MPa, the boost pressure is 60-80 MPa, and the holding time is 8-12 s.
[0019] Furthermore, in step 4, the solution treatment temperature is 545-550°C for 6-8h; after water quenching, aging treatment is performed at 200-205°C for 3-5h.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention provides a semi-solid die-casting aluminum alloy with high strength and good plasticity, which contains main elements such as silicon, magnesium, and copper. On this basis, the present invention adds titanium source, vanadium source, and antimony source; wherein, the addition of titanium element refines the α-A1 grains, improves the uniformity of components in the aluminum alloy, and improves the fluidity, strength, and plasticity of the aluminum alloy during the semi-solid die-casting process; the addition of vanadium element can refine and metamorphose the iron-rich phase from a coarse needle-like shape to a fine and uniform granular shape, eliminates the influence of the iron-rich phase on the strength and plasticity of the aluminum alloy, and significantly improves the strength and plasticity of the aluminum alloy during the semi-solid die-casting process; the addition of antimony element has a good refining and metamorphic effect on the eutectic silicon phase, and can transform the morphology of the eutectic silicon in the aluminum alloy from a slender needle-like shape to a fine and uniform granular shape, thereby improving the strength and plasticity of the aluminum alloy during the semi-solid die-casting process. By controlling the content of the above elements and impurity elements, they cooperate with each other to jointly improve the performance of the finished aluminum alloy.
[0021] When preparing aluminum alloy, boron-doped graphene loaded with cerium oxide is also added in the present invention. The preparation method of the boron-doped graphene loaded with cerium oxide is as follows: using graphene oxide and boric acid as raw materials, mixing the two and sintering at high temperature, realizing the reduction of graphene oxide and the doping of boron atoms in graphene, thereby obtaining boron-doped graphene; dispersing boron-doped graphene in ethylene glycol, adding cerium nitrate, and loading cerium oxide on the surface of boron-doped graphene by hydrothermal synthesis to obtain boron-doped graphene loaded with cerium oxide. After the conventional method directly adds graphene, the graphene is mainly distributed near the grain boundary, and the typical two-dimensional structure and wrinkle characteristic structure of graphene itself can effectively prevent the dislocation movement of the material during the force process, thereby achieving the enhancement effect, but this method has the problem of poor interface bonding strength between graphene and aluminum matrix, which will produce defects such as pores and slag inclusions. When boron-doped graphene loaded with cerium oxide is placed in a high-temperature molten liquid aluminum alloy body, the cerium oxide loaded on the graphene surface is reduced by aluminum to elemental cerium and aluminum oxide at high temperature. The reduced elemental cerium reacts with aluminum again to form a eutectic reaction, and the resulting product can be used as a nucleation particle for the primary phase, which has a significant refining effect on the aluminum alloy. Since the graphene is doped with boron, it not only has the effect of refining the grains, but also can react with the titanium element in the external titanium source to form titanium boride. The grains of titanium boride and aluminum oxide are small, which can be used as a reinforcing phase to improve the interface wettability problem between graphene and the aluminum alloy matrix material, further strengthen the bonding effect between graphene and the grain boundary, and is beneficial to improving the strength and plasticity of the aluminum alloy during the semi-solid die-casting process.
[0022] It should be noted that when preparing boron-doped graphene loaded with cerium oxide, if cerium oxide is first loaded on the graphene surface, it will affect the substitution of boron atoms for carbon atoms in the graphene, resulting in a decrease in the amount of boron doping. In addition, according to the two-dimensional mismatch theory, after the cerium oxide on the surface of the boron-doped graphene loaded with cerium oxide is reduced to elemental cerium, the elemental cerium reacts with aluminum to generate Al 11 Ce3 as a heterogeneous nucleation particle can achieve the most effective nucleation, while Al 11 The density of Ce3 is between 4.1 and 4.2 g / cm 3 The melt density is relatively large. If too much boron-doped graphene loaded with cerium oxide is added, the excess Al 11 Ce3 will segregate and precipitate, reducing the number of effective crystal nuclei, which will lead to a decrease in the refinement effect, and will increase the grain size, affecting the performance of the aluminum alloy. Therefore, the amount of boron-doped graphene loaded with cerium oxide is controlled to be 0.8-2% of the total weight of the aluminum alloy semi-solid slurry, and the prepared aluminum alloy has the best performance. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Materials and sources used in the present invention: Materials and sources used in the present invention: the silicon source is fast-melting silicon with a purity of ≥99.9%; the magnesium source is a magnesium ingot with a purity of ≥99.99%; the copper source is electrolytic copper with a purity of ≥99.99%; the aluminum source is an aluminum ingot with a purity of ≥99.85%; the titanium source is an Al-10Ti alloy; the vanadium source is an Al-5V alloy; the antimony source is an Al-10Sb alloy; and the graphene oxide is a single-layer graphene oxide with a sheet diameter of 0.5 to 5 μm.
[0025] Embodiment 1: A high-strength semi-solid die-casting aluminum alloy and a preparation method thereof, comprising the following steps:
[0026] Step 1: heating a silicon source, a magnesium source, a copper source, an aluminum source, a titanium source, a vanadium source, and an antimony source to 700° C. and melting them into a liquid state to obtain a liquid aluminum alloy; wherein the content of each element in the liquid aluminum alloy is, by weight percentage, 8.5% silicon, 0.5% magnesium, 0.2% copper, 0.07% titanium, 0.14% vanadium, 0.09% antimony, 0.15% iron, and the rest is aluminum and other impurity elements;
[0027] Step 2: Adding boron-doped graphene loaded with cerium oxide to the liquid aluminum alloy, heating to 1200° C., keeping the temperature for 200 minutes, and preparing an aluminum alloy semi-solid slurry at a temperature of 580° C. by a stirring and vibration method; wherein the amount of boron-doped graphene loaded with cerium oxide is 0.8% of the total weight of the aluminum alloy semi-solid slurry; the preparation method of the boron-doped graphene loaded with cerium oxide is:
[0028] S1: Graphene oxide and boric acid were mixed and ground at a mass ratio of 2:1 for 15 minutes; in a nitrogen environment, the temperature was raised to 900°C at a heating rate of 10°C / min, kept at this temperature for 60 minutes, and then naturally cooled, washed with ethanol, and vacuum dried to obtain boron-doped graphene;
[0029] S2: Adding boron-doped graphene to ethylene glycol, stirring magnetically for 15 minutes, and ultrasonically dispersing for 30 minutes to obtain a boron-doped graphene dispersion with a concentration of 1 mg / L; adding 15 g / L cerium nitrate solution to the boron-doped graphene dispersion, ultrasonically dispersing for 5 minutes, and then placing it in a drying oven for hydrothermal reaction at 130°C for 24 hours; after the reaction is completed, cooling and removing the supernatant, the obtained product is centrifuged, washed, dried, and ground, and then heated to 400°C at a heating rate of 2°C / min in an air atmosphere, and calcined for 3 hours to obtain boron-doped graphene loaded with cerium oxide; the content of each component in the boron-doped graphene loaded with cerium oxide is 25% cerium oxide and 75% boron-doped graphene by weight;
[0030] Step 3: die-casting the semi-solid aluminum alloy slurry to obtain a semi-solid die-cast aluminum alloy; wherein the die-casting temperature is 300° C., the injection speed is 1.5 m / s, the injection pressure ratio is 30 MPa, the boost pressure is 60 MPa, and the holding time is 12 s;
[0031] Step 4: subjecting the semi-solid die-casting aluminum alloy to a solution treatment at 545°C for 6 hours, subjecting the alloy to an aging treatment at 200°C for 3 hours after water quenching, and subjecting the alloy to a high-strength semi-solid die-casting aluminum alloy after furnace cooling.
[0032] Embodiment 2: A high-strength semi-solid die-casting aluminum alloy and a preparation method thereof, comprising the following steps:
[0033] Step 1: heating a silicon source, a magnesium source, a copper source, an aluminum source, a titanium source, a vanadium source, and an antimony source to 750° C. and melting them into a liquid state to obtain a liquid aluminum alloy; wherein the content of each element in the liquid aluminum alloy is, by weight percentage, 8.5% silicon, 0.5% magnesium, 0.2% copper, 0.07% titanium, 0.14% vanadium, 0.09% antimony, 0.15% iron, and the rest is aluminum and other impurity elements;
[0034] Step 2: Adding boron-doped graphene loaded with cerium oxide to the liquid aluminum alloy, heating to 1300° C., keeping the temperature for 220 minutes, and preparing an aluminum alloy semi-solid slurry at a temperature of 590° C. by a stirring and vibration method; wherein the amount of boron-doped graphene loaded with cerium oxide is 1.4% of the total weight of the aluminum alloy semi-solid slurry; the preparation method of the boron-doped graphene loaded with cerium oxide is:
[0035] S1: Graphene oxide and boric acid were mixed and ground in a mass ratio of 2:1 for 20 minutes; in a nitrogen environment, the temperature was raised to 950°C at a heating rate of 13°C / min, kept at this temperature for 85 minutes, and then naturally cooled, washed with ethanol, and vacuum dried to obtain boron-doped graphene;
[0036] S2: Adding boron-doped graphene to ethylene glycol, stirring magnetically for 20 minutes, and ultrasonically dispersing for 45 minutes to obtain a boron-doped graphene dispersion with a concentration of 1 mg / L; adding 15 g / L cerium nitrate solution to the boron-doped graphene dispersion, ultrasonically dispersing for 8 minutes, and then placing it in a drying oven at 140°C for hydrothermal reaction for 24 hours; after the reaction is completed, cooling and removing the supernatant, the obtained product is centrifuged, washed, dried, and ground, and then heated to 450°C at a heating rate of 4°C / min in an air atmosphere, and calcined for 3.5 hours to obtain boron-doped graphene loaded with cerium oxide; the content of each component in the boron-doped graphene loaded with cerium oxide is 25% cerium oxide and 75% boron-doped graphene by weight;
[0037] Step 3: die-casting the semi-solid aluminum alloy slurry to obtain a semi-solid die-cast aluminum alloy; wherein the die-casting temperature is 330° C., the injection speed is 2 m / s, the injection pressure ratio is 40 MPa, the boost pressure is 70 MPa, and the holding time is 10 s;
[0038] Step 4: subjecting the semi-solid die-casting aluminum alloy to solution treatment at 545°C for 7 hours, subjecting the alloy to aging treatment at 205°C for 4 hours after water quenching, and subjecting the alloy to furnace cooling to obtain a high-strength semi-solid die-casting aluminum alloy.
[0039] Embodiment 3: A high-strength semi-solid die-casting aluminum alloy and a preparation method thereof, comprising the following steps:
[0040] Step 1: heating a silicon source, a magnesium source, a copper source, an aluminum source, a titanium source, a vanadium source, and an antimony source to 800° C. and melting them into a liquid state to obtain a liquid aluminum alloy; wherein the content of each element in the liquid aluminum alloy is, by weight percentage, 8.5% silicon, 0.5% magnesium, 0.2% copper, 0.07% titanium, 0.14% vanadium, 0.09% antimony, 0.15% iron, and the rest is aluminum and other impurity elements;
[0041] Step 2: Adding boron-doped graphene loaded with cerium oxide to the liquid aluminum alloy, heating to 1400° C., keeping the temperature for 240 minutes, and preparing an aluminum alloy semi-solid slurry at a temperature of 600° C. by a stirring and vibration method; wherein the amount of boron-doped graphene loaded with cerium oxide is 2% of the total weight of the aluminum alloy semi-solid slurry; the preparation method of the boron-doped graphene loaded with cerium oxide is:
[0042] S1: Graphene oxide and boric acid were mixed and ground at a mass ratio of 2:1 for 30 minutes; in a nitrogen environment, the temperature was raised to 1000°C at a heating rate of 15°C / min, kept at this temperature for 90 minutes, and then naturally cooled, washed with ethanol, and vacuum dried to obtain boron-doped graphene;
[0043] S2: Adding boron-doped graphene to ethylene glycol, stirring by magnetic force for 30 minutes, and ultrasonically dispersing for 60 minutes to obtain a boron-doped graphene dispersion with a concentration of 1 mg / L; adding 15 g / L cerium nitrate solution to the boron-doped graphene dispersion, ultrasonically dispersing for 5 minutes, and then placing it in a drying oven for hydrothermal reaction at 150°C for 24 hours; after the reaction is completed, cooling and removing the supernatant, the obtained product is centrifuged, washed, dried, and ground, and then heated to 500°C at a heating rate of 5°C / min in an air atmosphere, and calcined for 4 hours to obtain boron-doped graphene loaded with cerium oxide; the content of each component in the boron-doped graphene loaded with cerium oxide is 25% cerium oxide and 75% boron-doped graphene by weight;
[0044] Step 3: die-casting the semi-solid aluminum alloy slurry to obtain a semi-solid die-cast aluminum alloy; wherein the die-casting temperature is 350° C., the injection speed is 2.5 m / s, the injection pressure ratio is 50 MPa, the boost pressure is 80 MPa, and the holding time is 12 s;
[0045] Step 4: subjecting the semi-solid die-casting aluminum alloy to solution treatment at 550°C for 8 hours, subjecting the alloy to aging treatment at 205°C for 5 hours after water quenching, and subjecting the alloy to furnace cooling to obtain a high-strength semi-solid die-casting aluminum alloy.
[0046] Comparative Example 1: The order of loading cerium oxide and boron doping in the scheme was adjusted, and the other parameters were the same as those in Example 1.
[0047] Step 1: heating a silicon source, a magnesium source, a copper source, an aluminum source, a titanium source, a vanadium source, and an antimony source to 700° C. and melting them into a liquid state to obtain a liquid aluminum alloy; wherein the content of each element in the liquid aluminum alloy is, by weight percentage, 8.5% silicon, 0.5% magnesium, 0.2% copper, 0.07% titanium, 0.14% vanadium, 0.09% antimony, 0.15% iron, and the rest is aluminum and other impurity elements;
[0048] Step 2: Adding boron-doped graphene loaded with cerium oxide to the liquid aluminum alloy, heating to 1200° C., keeping the temperature for 200 minutes, and preparing an aluminum alloy semi-solid slurry at a temperature of 580° C. by a stirring and vibration method; wherein the amount of boron-doped graphene loaded with cerium oxide is 0.8% of the total weight of the aluminum alloy semi-solid slurry; the preparation method of the boron-doped graphene loaded with cerium oxide is:
[0049] S1: Add graphene oxide to ethylene glycol, stir magnetically for 15 minutes, and disperse ultrasonically for 30 minutes to obtain a graphene oxide dispersion with a concentration of 1 mg / L; add 15 g / L cerium nitrate solution to the graphene oxide dispersion, disperse ultrasonically for 5 minutes, and then place it in a drying oven for hydrothermal reaction at 130°C for 24 hours; after the reaction is completed, cool and remove the supernatant, centrifuge, wash, dry, and grind the obtained product, and then heat it to 400°C at a heating rate of 2°C / min in an air atmosphere, and calcine it at this temperature for 3 hours to obtain cerium oxide-loaded graphene oxide; in the cerium oxide-loaded graphene oxide, the content of each component is 25% cerium oxide and 75% graphene oxide by weight;
[0050] S2: Grinding the cerium oxide loaded graphene oxide and boric acid at a mass ratio of 2:1 for 15 minutes; heating to 900°C at a heating rate of 10°C / min in a nitrogen environment, keeping the temperature for 60 minutes and then cooling naturally, washing with ethanol, and vacuum drying to obtain the cerium oxide loaded boron-doped graphene;
[0051] Step 3: die-casting the semi-solid aluminum alloy slurry to obtain a semi-solid die-cast aluminum alloy; wherein the die-casting temperature is 300° C., the injection speed is 1.5 m / s, the injection pressure ratio is 30 MPa, the boost pressure is 60 MPa, and the holding time is 12 s;
[0052] Step 4: subjecting the semi-solid die-casting aluminum alloy to a solution treatment at 545°C for 6 hours, subjecting the alloy to an aging treatment at 200°C for 3 hours after water quenching, and subjecting the alloy to a high-strength semi-solid die-casting aluminum alloy after furnace cooling.
[0053] Comparative Example 2: Only graphene was added, and the other parameters were the same as those in Example 2.
[0054] Step 1: heating a silicon source, a magnesium source, a copper source, an aluminum source, a titanium source, a vanadium source, and an antimony source to 750° C. and melting them into a liquid state to obtain a liquid aluminum alloy; wherein the content of each element in the liquid aluminum alloy is, by weight percentage, 8.5% silicon, 0.5% magnesium, 0.2% copper, 0.07% titanium, 0.14% vanadium, 0.09% antimony, 0.15% iron, and the rest is aluminum and other impurity elements;
[0055] Step 2: adding graphene to the liquid aluminum alloy, heating it to 1300°C, keeping it warm for 220 minutes, and preparing an aluminum alloy semi-solid slurry with a temperature of 590°C by a stirring and vibration method; wherein the amount of graphene is 1.4% of the total weight of the aluminum alloy semi-solid slurry; the preparation method of the graphene is: taking graphene oxide, heating it to 950°C at a heating rate of 13°C / min in a nitrogen environment, keeping it warm for 85 minutes, and then naturally cooling it to obtain graphene;
[0056] Step 3: die-casting the semi-solid aluminum alloy slurry to obtain a semi-solid die-cast aluminum alloy; wherein the die-casting temperature is 330° C., the injection speed is 2 m / s, the injection pressure ratio is 40 MPa, the boost pressure is 70 MPa, and the holding time is 10 s;
[0057] Step 4: subjecting the semi-solid die-casting aluminum alloy to solution treatment at 545°C for 7 hours, subjecting the alloy to aging treatment at 205°C for 4 hours after water quenching, and subjecting the alloy to furnace cooling to obtain a high-strength semi-solid die-casting aluminum alloy.
[0058] Comparative Example 3: The amount of boron-doped graphene loaded with cerium oxide was increased, and the other parameters were the same as those in Example 3.
[0059] Step 1: heating a silicon source, a magnesium source, a copper source, an aluminum source, a titanium source, a vanadium source, and an antimony source to 800° C. and melting them into a liquid state to obtain a liquid aluminum alloy; wherein the content of each element in the liquid aluminum alloy is, by weight percentage, 8.5% silicon, 0.5% magnesium, 0.2% copper, 0.07% titanium, 0.14% vanadium, 0.09% antimony, 0.15% iron, and the rest is aluminum and other impurity elements;
[0060] Step 2: Adding boron-doped graphene loaded with cerium oxide to the liquid aluminum alloy, heating to 1400° C., keeping the temperature for 240 minutes, and then using a stirring and vibration method to prepare an aluminum alloy semi-solid slurry at a temperature of 600° C.; wherein the amount of boron-doped graphene loaded with cerium oxide is 4% of the total weight of the aluminum alloy semi-solid slurry; the preparation method of the boron-doped graphene loaded with cerium oxide is:
[0061] S1: Graphene oxide and boric acid were mixed and ground at a mass ratio of 2:1 for 30 minutes; in a nitrogen environment, the temperature was raised to 1000°C at a heating rate of 15°C / min, kept at this temperature for 90 minutes, and then naturally cooled, washed with ethanol, and vacuum dried to obtain boron-doped graphene;
[0062] S2: Adding boron-doped graphene to ethylene glycol, stirring by magnetic force for 30 minutes, and ultrasonically dispersing for 60 minutes to obtain a boron-doped graphene dispersion with a concentration of 1 mg / L; adding 15 g / L cerium nitrate solution to the boron-doped graphene dispersion, ultrasonically dispersing for 5 minutes, and then placing it in a drying oven for hydrothermal reaction at 150°C for 24 hours; after the reaction is completed, cooling and removing the supernatant, the obtained product is centrifuged, washed, dried, and ground, and then heated to 500°C at a heating rate of 5°C / min in an air atmosphere, and calcined for 4 hours to obtain boron-doped graphene loaded with cerium oxide; the content of each component in the boron-doped graphene loaded with cerium oxide is 25% cerium oxide and 75% boron-doped graphene by weight;
[0063] Step 3: die-casting the semi-solid aluminum alloy slurry to obtain a semi-solid die-cast aluminum alloy; wherein the die-casting temperature is 350° C., the injection speed is 2.5 m / s, the injection pressure ratio is 50 MPa, the boost pressure is 80 MPa, and the holding time is 12 s;
[0064] Step 4: subjecting the semi-solid die-casting aluminum alloy to solution treatment at 550°C for 8 hours, subjecting the alloy to aging treatment at 205°C for 5 hours after water quenching, and subjecting the alloy to furnace cooling to obtain a high-strength semi-solid die-casting aluminum alloy.
[0065] Comparative Example 4: Boron-doped graphene loaded with cerium oxide was not added, and other parameters were the same as those in Example 3.
[0066] Step 1: heating a silicon source, a magnesium source, a copper source, an aluminum source, a titanium source, a vanadium source, and an antimony source to 800° C. and melting them into a liquid state to obtain a liquid aluminum alloy; wherein the content of each element in the liquid aluminum alloy is, by weight percentage, 8.5% silicon, 0.5% magnesium, 0.2% copper, 0.07% titanium, 0.14% vanadium, 0.09% antimony, 0.15% iron, and the rest is aluminum and other impurity elements;
[0067] Step 2: preparing a semi-solid aluminum alloy slurry at a temperature of 600° C. by a stirring and vibration method;
[0068] Step 3: die-casting the semi-solid aluminum alloy slurry to obtain a semi-solid die-cast aluminum alloy; wherein the die-casting temperature is 350° C., the injection speed is 2.5 m / s, the injection pressure ratio is 50 MPa, the boost pressure is 80 MPa, and the holding time is 12 s;
[0069] Step 4: subjecting the semi-solid die-casting aluminum alloy to solution treatment at 550°C for 8 hours, subjecting the alloy to aging treatment at 205°C for 5 hours after water quenching, and subjecting the alloy to furnace cooling to obtain a high-strength semi-solid die-casting aluminum alloy.
[0070] Experiment: The semi-solid die-cast aluminum alloys prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to performance tests, including tensile strength, yield strength, and elongation; the test method was based on the standard GB / T 16865-2023, and the aluminum alloys of Examples 1 to 3 and Comparative Examples 1 to 4 were processed into standard tensile specimens, and tensile mechanical properties were tested on an electronic tensile testing machine. The test environment temperature was 25°C, the tensile rate was 2mm / min, and each group of samples was tested three times and the average value was taken. The experimental results are shown in the following table.
[0071]
[0072]
[0073] Conclusion: The data of Examples 1 to 3 show that the semi-solid die-cast aluminum alloy prepared by the present invention has good mechanical properties, with a tensile strength greater than 300MPa, a yield strength greater than 260MPa, and an elongation greater than 10%. The data of Example 1 and Comparative Example 1 show that after changing the preparation process of boron-doped graphene loaded with cerium oxide, its modification effect on the performance of aluminum alloy will become worse; the data of Example 2 and Comparative Example 2 show that boron-doped graphene loaded with cerium oxide is a further modification of graphene, and its reinforcing effect on aluminum alloy is significantly better than that of unmodified graphene; the data of Example 3 and Comparative Example 3 show that excessive use of boron-doped graphene loaded with cerium oxide will also lead to a decrease in the performance of aluminum alloy; the data of Example 3 and Comparative Example 4 show that after adding boron-doped graphene loaded with cerium oxide, the performance of aluminum alloy is significantly improved.
[0074] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-strength semi-solid die-casting aluminum alloy, characterized in that: The following steps are involved: Step 1: Heat the silicon source, magnesium source, copper source, aluminum source, titanium source, vanadium source, and antimony source to 700-800° C. and melt them into liquid state to obtain a liquid aluminum alloy; Step 2: Adding boron-doped graphene loaded with cerium oxide to the liquid aluminum alloy, heating to 1200-1400° C., keeping the temperature for 200-240 minutes, and then preparing an aluminum alloy semi-solid slurry at a temperature of 580-600° C. by a stirring and vibration method; wherein the amount of boron-doped graphene loaded with cerium oxide is 0.8-2% of the total weight of the aluminum alloy semi-solid slurry; the content of each component in the boron-doped graphene loaded with cerium oxide is, by weight percentage, 25-45% cerium oxide and 55-75% boron-doped graphene; Step 3: die-casting the semi-solid aluminum alloy slurry to obtain a semi-solid die-cast aluminum alloy; Step 4: subjecting the semi-solid die-cast aluminum alloy to a solution treatment, water quenching and then an aging treatment, and cooling in the furnace to obtain a high-strength semi-solid die-cast aluminum alloy.
2. The method for preparing a high-strength semi-solid die-casting aluminum alloy according to claim 1, characterized in that: In step 1, the contents of various elements in the liquid aluminum alloy, by weight percentage, are 6-9.5% silicon, 0.3-0.65% magnesium, 0.15-0.25% copper, 0.06-0.09% titanium, 0.1-0.18% vanadium, 0.05-0.12% antimony, 0.01-0.2% iron, and the rest are aluminum and other impurity elements.
3. The method for preparing a high-strength semi-solid die-casting aluminum alloy according to claim 1, characterized in that: In step 2, the preparation method of boron-doped graphene loaded with cerium oxide is: S1: After the graphene oxide and boric acid are mixed and ground for 15-30 minutes, the temperature is raised to 900-1000°C at a heating rate of 10-15°C / min in a nitrogen environment, and the mixture is kept at this temperature for 60-90 minutes and then naturally cooled, washed with ethanol, and vacuum dried to obtain boron-doped graphene; S2: Add boron-doped graphene to ethylene glycol, stir magnetically for 15-30 minutes, and ultrasonically disperse for 30-60 minutes to obtain a boron-doped graphene dispersion; add cerium nitrate solution to the boron-doped graphene dispersion, ultrasonically disperse for 5-10 minutes, and then place it in a drying oven for hydrothermal reaction at 130-150°C for 24 hours; after the reaction is completed, cool and remove the supernatant, centrifuge, wash, dry, and grind the product, and then heat it to 400-500°C at a heating rate of 2-5°C / min in an air atmosphere, and calcine it at this temperature for 3-4 hours to obtain boron-doped graphene loaded with cerium oxide.
4. The method for preparing a high-strength semi-solid die-casting aluminum alloy according to claim 3, characterized in that: In S1, graphene oxide and boric acid are mixed and ground in a mass ratio of (2-2.2):
1.
5. The method for preparing a high-strength semi-solid die-casting aluminum alloy according to claim 3, characterized in that: In S2, the concentration of the boron-doped graphene dispersion is 1-2 mg / mL; the concentration of the cerium nitrate solution is 10-20 g / mL.
6. The method for preparing a high-strength semi-solid die-casting aluminum alloy according to claim 1, characterized in that: In step 3, the die-casting temperature is 300-350°C, the injection speed is 1.5-2.5 m / s, the injection pressure ratio is 30-50 MPa, the boost pressure is 60-80 MPa, and the holding time is 8-12 s.
7. The method for preparing a high-strength semi-solid die-casting aluminum alloy according to claim 1, characterized in that: In step 4, the solution treatment temperature is 545-550°C for 6-8 hours; after water quenching, aging treatment is performed at 200-205°C for 3-5 hours.
8. A high-strength semi-solid die-casting aluminum alloy prepared according to the preparation method of any one of claims 1 to 7.
Citation Information
Patent Citations
Semi-solid die casting and high-strength-and-toughness aluminum alloy and manufacturing method thereof
CN108286001A
Preparation method for cerium oxide coated graphene oxide aluminum product semi-solid blank
CN111286634A
Boron-doped graphene reinforced copper-based composite material and preparation method thereof
CN112877562A